ANALISIS KOMPARASI ANTARA PERLINDUNGAN PATEN BIASA DENGAN PATEN SEDERHANA BERDASARKAN UNDANG-UNDANG PATEN - Erlina B; Melisa Safitri (PRANATA HUKUM, 2020)
This journal discusses the comparison of legal protections against ordinary patents with simple patents in the patent legal system in Indonesia. The method of normative juridical research is descriptive with a statutory approach supported by a theoretical approach, namely by studying and reviewing the provisions of Law No. 13 of 2016 on patents with legal theory to know the comparison of legal protections against ordinary patents and simple patents in the patent legal system in Indonesia.